Інтертекстуальність як ознака стилю Валерія Шевчука - Козачук, Н. (Питання літературознавства, 2009)
Розглядається інтертекстуальність як своєрідна ознака творчості Валерія Шевчука. Найчастіше автор використовує інтерпретацію біблійних легенд, опосередковані ремінісценції – пародії, алюзії, перифрази. Вдаючись до інтертекстуальності, письменник вимагає ерудованого читача, здатного розпізнати вкраплення „чужих” текстів, які майстерно завуальовані, приховані. The focus of the study is intertextuality as the feature of Valerij Shevchuk’s creative work. Biblical legends interpreted by the author and indirect reminiscences – parody, allusion, periphrasis are the devices the author uses most often. Resorting to intertextuality requires an erudite reader who is able to recognize inclusions of the cited texts skillfully disguised and hidden.